Can CoP theory be applied? Exploring praxis in a community of practice on gender - Bailey, Arwen (KM4Dev-community, 2017)
Kurt Lewin, father of social learning theory, once stated ‘There is nothing so practical as a good theory’. Communities of Practice are widely recognized and promoted as vehicles for learning in and across organizations. However it has been well documented that it is easier to describe their existence than to use that knowledge to bring one into being. Various authors have explored and described factors that seem useful to make a CoP work. The context is an agricultural research-for-development organization, in which low gender capacity at institutional level had been identified as a weakness that needed addressing. The author followed step by step the advice laid out by scholars and practitioners of CoP theory to explore whether engaging in ‘praxis’ (i.e. the enactment of a theory) would be effective to nurture a CoP to raise gender research capacity. After 18 months of being nurtured according to theory, the CoP may be considered successful for this point in its history. It has an identity, regular meetings in which experiences are shared and problems discussed, increasing membership and a growing number of products generated by and shared among its membership. The implications of this case study are that careful study of the theory can lead to better practice and more effective learning. The steps taken to go from theory to practice, outlined in this paper, may be useful to other aspiring CoP practitioners.